Caught out! The role of customer emotional intelligence and dual thinking processes in perceptions of frontline service employees' inauthentic positive displays. Issue 12 (9th August 2021) - Wang, Karyn L.; Nguyen, Helena; Johnson, Anya; Groth, Markus
Abstract: Frontline service employees often feign positive displays during customer interactions to enhance service outcomes, but to what extent are customers aware of these inauthentic positive displays? The perception of inauthenticity involves a series of complex judgments, however, the influence of customers' different thinking processes on these judgments and the role of customer individual differences in emotional intelligence are seldom investigated. This article investigates how customer emotional intelligence influences the processing of frontline employees' inauthentic positive displays. Across three experimental studies, we find that experiential processes combine with high emotional intelligence to predict more accurate perceptions of frontline employees' inauthentic positive displays (Study 1). In contrast, rational processes interact with low emotional intelligence to predict less accurate perceptions (Study 2). We also find that high emotional intelligence and high dual thinking processes (both experiential and rational) predict more accurate perceptions of frontline employees' inauthentic positive displays (Study 3). These results extend knowledge of the important role of customers in detecting the frontline employee's inauthentic displays. Our findings have important practical implications for service settings where there are strong expectations for frontline employees to provide "service with a smile."